Investing Time for Your In-Game Boyfriends and BFFs: Time as Commodity and the Simulation of Emotional Labor in Mystic Messenger. Issue 2 (March 2019) - Ganzon, Sarah Christina
Mystic Messenger is a real-time mobile dating simulator and otome game that simulates how people fall in love online. In this essay, I will look at significant parallels between casual games and otome games and point out the ways in which both define women as players and consumers of games. By focusing on Mystic Messenger, I examine the ways in which the game's real-time simulation of emotional labor becomes a way of policing women's desires, a way of reinforcing nurturing roles over women's desires, and a way of literally commodifying the assumedly female player's leisure time. Furthermore, I also examine player practices and discussions of cheating within the player community, tagging these as light forms of resistances and ways in which various individuals in the community assert their identity and their agency over their own time.